International politics enduring concepts and contemporary issues - Art, Robert J.; Jervis, Robert, 1940- (Prentice Hall, 2013)
International Politics places contemporary essays alongside classics to survey the field's diverse voices, concepts, and issues. Edited by two of the most respected international relations scholars,International Politics challenges readers to use original scholarship to recognize and analyze patterns in world politics. This bestselling reader considers how to effectively understand politics under governments and beyond. Carefully edited selections cover the most essential topics and are put into conversation with each other to illustrate fundamental debates and differing points of view. Comprehensive and engaging, International Politics offers the best overview of the discipline as well as the forces shaping the world today.